2017
DOI: 10.7860/jcdr/2017/24658.9982
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Individual Factors, Socioeconomic and Social Participation on Individual Happiness: A Cross-Sectional Study

Abstract: INTRODUCTIONHappiness is one of the most important values [1] that always has been associated with pleasure, optimism and hope [2]. In fact, the happiness is an inner state that is derived from human judgment and experience [3,4]. Eysenck believes that happiness is a collection of fun, a combination of maximum positive effect and the least negative emotion without pain. Happiness and vitality are the most essential human innate desires and psychological need. So happiness and its determinants, has been conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 4 publications
3
15
0
5
Order By: Relevance
“…The impact of educational attainment on changing drinking patterns [ 17 ], BMI, insomnia, physical activity [ 17 ], depression [ 20 ], suicidal behaviors [ 33 ], and mortality [ 24 ] are all shown to be smaller for Blacks than for Whites. Similar results are seen in the transgenerational effects of parental education on child outcomes [ 21 , 22 , 27 , 65 ].…”
Section: Discussionsupporting
confidence: 70%
“…The impact of educational attainment on changing drinking patterns [ 17 ], BMI, insomnia, physical activity [ 17 ], depression [ 20 ], suicidal behaviors [ 33 ], and mortality [ 24 ] are all shown to be smaller for Blacks than for Whites. Similar results are seen in the transgenerational effects of parental education on child outcomes [ 21 , 22 , 27 , 65 ].…”
Section: Discussionsupporting
confidence: 70%
“…De igual manera un estudio realizado con jubilados de Taipéi, Taiwán, encontró que las buenas relaciones familiares predicen una mayor felicidad; y esta a la vez es una variable mediadora entre las relaciones y la salud percibida (31). A una conclusión similar llegaron Azizi et al (32), quienes documentaron que las buenas relaciones con los demás (familia, parientes y amigos) aumentan la felicidad.…”
Section: Discussionunclassified
“…It can be said that in most circumstances, individuals with higher economic status experience lower anxiety and stress in their lifetime. [ 9 ] It seems that better family economic status can increase life satisfaction by enhancing the social support, increasing the possibility to access the needs, desires, solving problems, and opportunities to achieve one's preferred activities. However, this discrepancy could be due to cultural differences in reporting the economic situation in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Review of related literature revealed that pleasant relations with others, including relatives friends and family, is a key element and one of the most vital factors to attain life satisfaction and happiness. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%